Green technology: synthesis of iron-modified biochar derived from pine cones to remove azithromycin and ciprofloxacin from water - Aziz, Sadia; Anbreen, Sundus; Iftikhar, Iqra; Fatima, Tabassum; Iftikhar, Aqsa; Ali, Liaqat (Frontiers in Environmental Science, 2024)
The rise of antibiotic pollutants in water poses a threat to ecosystems and human health. Iron modified biochar exhibiting adsorption properties, offers promising approach for effective environmental remediation. Current study explored the potential of iron loaded biochar synthesized from pine cones for antibiotics removal from water. In this study, pines cones, a sustainable and renewable source was used to produce iron modified biochar and employed for removal of Azithromycin, Ciprofloxacin and their mixture from aqueous solutions.Biochar was synthesized through pyrolysis and modified by addition of iron salts. The analysis of iron modified biochar by Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and scanning electron microscopy (SEM), suggested it a crystalline structure rich in minerals, functional groups (O-H, C=O, and C≡C) and loaded with iron, having plate-like roughness and distorted morphology along with sharp edges and corners.Antibiotic removal was evaluated by changing different physical parameters i.e., biochar dose, pH, and temperature. Maximum removal percentages of azithromycin, ciprofloxacin and their mixture were obtained as 87.8%, 91.3% and 84% respectively at low pH, low Femodified biochar dose and higher temperature. Application of kinetic models suggested that adsorption of antibiotics on iron modified biochar is more inclined towards pseudo-second order (R 2 > 0.98) indicating a chemisorption nature of the adsorption process. The findings highlight the potential of iron modified biochar for antibiotic removal from aqueous solutions.